Nest cycle and nestling development of a pair of Changeable Hawk-Eagles Nisaetus cirrhatus in Gunung Halimun-Salak National Park, West Java - . Gunawan; Seva Nazar; Richard A Noske (Indonesian Ornithologists’ Union, 2017)
We monitored nesting of a pair of Changeable Hawk-Eagles Nisaetus cirrhatus at Gunung Halimun–Salak National Park, West Java, in two consecutive years (2012 and 2013). The single egg was laid in July in the first year, and June in the second. This is consistent with data from the early 20th Century which suggests these are the peak laying months for Java. Contrary to the literature, both sexes took part in incubation, though the female incubated more frequently. The incubation and nestling periods were estimated to be c.50 days and 62 days, respectively, but as neither laying nor hatching was observed directly, it is possible that the first period is over-estimated, and the second, under-estimated. The combined period (112 days) is consistent with the minimum estimate of 108 days in the literature. The body length (including tail) of the 2013 eaglet grew at an average rate of c. 6 cm per week. Of 21 prey items brought to the nest by the adults, 13 (62%) were reptiles, and only three were mammals.